DOKUMEN ELEKTRONIK SEBAGAI ALAT BUKTI DALAM HUKUM ACARA PERDATA DI INDONESIA - Moh Nafri (Maleo Law Journal, 2019)
The development of information technology that is increasingly rapidly influencing aspects of people's lives both in terms of economic, social and cultural. so that in conducting transactions in the field of commerce was also done through internet access. The issue that arises and is regulated in the ITE Law is related to how the basis for regulating the use of electronic documents as evidence in civil procedural law in Indonesia and how the strength of proof of electronic documents as evidence in Indonesian civil procedural law. The research used is a normative legal research method. The normative legal research approach is by reviewing the regulations relating to this research, namely the regulations regarding electronic documents as evidence. The results of the study found that the electronic documents regulated in the ITE Law both before birth and after the birth of this law have been recognized in various laws. However, in the regulation of other laws not explicitly referred to as "electronic documents". In the other law mentioned herein are types of electronic documents which have a legal position as evidence in a trial. The coming into effect of the ITE Law, in addition to the evidence contained in the HIR, RBg and KUHAPer, electronic evidence is also valid as evidence.Keyword: Electronic Documents, Proof